The inflammatory potential of diet in adults with knee osteoarthritis: sex-specific associations with quality of life, sleep, fatigue and mental health - Law, Lynette; Heerey, Joshua J.; Devlin, Brooke L.; Brukner, Peter; De Livera, Alysha M.; Hebert, James R.; Price, Sherry; White, Nathan P.; Culvenor, Adam G. (Frontiers in Nutrition, 2025)
BackgroundKnee osteoarthritis (OA) is a disabling condition—characterized by pain, stiffness, and impaired quality of life—that affects more females than males. Chronic systemic inflammation is a key feature of knee OA and can be modulated by diet. We evaluated the sex-specific relationship between the inflammatory potential of diet and health-related quality of life (HRQOL), sleep quality, energy and fatigue levels, and psychological distress in individuals with knee OA.MethodsThis cross-sectional study analyzed baseline data from 144 participants (64% female) aged 45–85 years with symptomatic knee OA enrolled in the FEAST (eFEct of an Anti-inflammatory diet for knee oSTeoarthritis) randomized controlled trial, which compared an anti-inflammatory dietary program to a standard low-fat dietary program. Dietary inflammatory potential was assessed using the dietary inflammatory index (DII®) and energy-adjusted DII (E-DII™), calculated from 3-day food diaries. Higher scores reflect more proinflammatory diets. Outcomes were HRQOL (EQ-5D-5L utility score and 100 mm visual analogue scale [VAS]), self-reported sleep quality, energy and fatigue levels (100 mm VAS), and psychological distress (Kessler Scale). Linear regression with interaction terms assessed sex-specific associations between DII/E-DII and outcomes, adjusting for age and body mass index (BMI).ResultsMale and female participants had a mean ± standard deviation BMI of 30.4 ± 3.8 and 30.2 ± 7.2 kg/m2, respectively. Mean E-DII and DII were −0.35 ± 1.34 and 0.72 ± 1.49 (females), and −0.26 ± 1.52 and 0.33 ± 1.45 (males). Higher E-DII scores were associated with lower EQ-5D utility scores in females (unadjusted β = −0.03, 95% CI −0.05 to −0.001), but not after adjustment. Higher DII scores were associated with lower energy levels in males (unadjusted β = −4.34, 95% CI −8.44 to −0.23; adjusted β = −4.01, 95% CI −7.91 to −0.30). No associations were found between DII and HRQOL, sleep, fatigue, or psychological distress in either sex.ConclusionNo associations were found between dietary inflammatory potential and sleep quality, fatigue, or psychological distress. A more proinflammatory diet was linked to lower energy levels in males with symptomatic knee OA. Findings from the FEAST trial will clarify whether reducing dietary inflammation improves these outcomes over time.